Unusual Operation of the Junction Transistor Based on Dynamical Behavior of Impurities - Roberto Baca Arroyo (Advances in Condensed Matter Physics)
The dynamical behavior of impurities into the silicon junction transistor has been studied using an empirical methodology to investigate its behavior knowing only the physical parameters of materials together with practical behavior of their passive components. The operating modes suggested with equations governing circuit performance are derived considering transient analysis. The relationship between material properties and equivalent circuit is discussed from a physical viewpoint. Theoretical solution of the equations yields a graphical response as approximation of the experimental results obtained from a proposed circuit built with an inductor and an NPN silicon MPSH10 transistor. Hence, the impurities-controlled electrical properties indicate that the observed unusual operation can be a good strategy to optimize signal processing in electronics.